Investing in blockchain technologies and digital assets: accounting perspectives - Miloš Grujić; Željko Vojinović (Anali Ekonomskog fakulteta u Subotici, 2024)
This paper examines the complex landscape of digital currencies, non-fungible tokens (NFTs), and distributed ledger technology (DLT), focusing on their implications within the accounting and financial reporting sector. The surge in popularity of these assets has brought about reporting challenges and complexities. The lack of comprehensive accounting standards and the digitization of financial reporting processes further compound the situation. These challenges underscore the need to update accounting practices to align with the security and transparency offered by DLT. The study examines the International Financial Reporting Standards (IFRS) for digital currency reporting, analyzing their implications and potential solutions for the accounting community. Central to this exploration is the question: How can the accounting sector navigate the multifaceted challenges and harness the multifarious opportunities that stem from digital currencies, NFTs, and DLT? Using a comprehensive research approach, including a literature review, empirical analysis, case studies, and comparative analysis, this study identifies strategies for managing the reporting complexities of digital assets. It also highlights the importance of collaborative dialogue between stakeholders and regulators to ensure consistency in an evolving landscape. This paper guides the accounting and investment sector in making informed decisions, fortified by a nuanced understanding of the evolving digital asset terrain.